Procedural modelling of urban environments - Cullen, Brian (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2012)
Procedural modelling of urban environments has become an important topic in computer graphics. With the ever increasing demand for larger and more realistic content in games and movies, the time and cost to model urban content by hand is becoming unfeasible. Apart from the entertainment industry, large urban models are also desired for urban planning applications and emergency response training.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.